2009
DOI: 10.3109/09638280902980910
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of home rehabilitation after hip fracture – 1-year follow-up of functioning, balance confidence, and health-related quality of life in elderly people

Abstract: The positive long-term effects were more pronounced among the participants in the HR group than among those who received CC, possibly due to the early start of the HR programme in hospital and its focus on self-efficacy and training of daily activities. However, one year after discharge a mojority of participants in both groups did not consider themselves to be fully recovered when they compared to their situation before the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 52 publications
7
87
0
8
Order By: Relevance
“…A large number of the participants had some or major difficulty in ADL and IADL after the hip fracture. Similar to the other studies most of the recovery in physical functioning occurred within the first three months after hospital discharge (10,26). Some of this recuperation is presumably natural and may occur without any intervention.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A large number of the participants had some or major difficulty in ADL and IADL after the hip fracture. Similar to the other studies most of the recovery in physical functioning occurred within the first three months after hospital discharge (10,26). Some of this recuperation is presumably natural and may occur without any intervention.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, previously only two RCTs have indicated that individually tailored multicomponent home-based rehabilitation program has improved independence in daily activities after a hip fracture (10,28). Anyhow, in these studies the interventions started when the participants were staying at geriatric wards and hospital staff was involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten previous studies on seven different trials have been conducted (Crotty et al 2002, Crotty et al 2003, Latham et al 2014, Shyu et al 2010, Tinetti et al 1999, Tseng, Shyu & Liang 2012, Ziden, Frandin & Kreuter 2008, Ziden, Kreuter & Frandin 2010, but evidence of the effects on mobility limitation and disability remains conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…These results somewhat contrast with the promising results from studies on early supported discharge (ESD) and home rehabilitation programs, which show similar or better outcomes of patient treatment when the length of specialist health care stay is reduced (23,(42)(43)(44)(45)(46). However, particular ESD studies presuppose extra SpHC effort in patient transition, performed in the PrHC setting, offering close collaboration and support in the homecoming phase (21,22).…”
Section: Discussionmentioning
confidence: 86%